Transcriptome profilling analysis characterized the gene expression patterns responded to combined drought and heat stresses in soybean. (December 2018) - Wang, Libin; Liu, Lijun; Ma, Yuling; Li, Shuang; Dong, Shoukun; Zu, Wei
Graphical abstract: Highlights: Combining dynamic changing SOD, MDA, soluble sugar and proline contents and the degree of leaf damage under stress, samples of 8 h and 24 h after heat, drought and combined stress treatments were selected for RNA-seq. The RNA sequencing analysis demonstrated that many genes involved in the defense response, photosynthesis, metabolic process, etc. are differentially expressed in response to drought and heat. However, 1468 and 1220 upregulated and 1146 and 686 downregulated genes were confirmed as overlapping differentially expressed genes at 8 h and 24 h after treatment, and these genes are mainly involved in transport, binding and defense responses. Comparison of single and combined stress suggests the combined stress did not result in a simple additive response, and that there may be a synergistic response to the combination of drought and heat in soybean. TFs in the single and combination stress were identified from DEGs, which classified into 9 clusters according to expression levels of six treatment and one control groups, revealed dynamic changing TF expression profiles and molecular mechanisms in response to single and combination stress. Abstract: Heat and drought are the two major abiotic stress limiting soybean growth and output worldwide. Knowledge of the molecular mechanisms underlying the responses to heat, drought, and combined stress is essential for soybean molecular breeding. In this study, RNA-sequencing was used to determine the transcriptional responses of soybean to heat, drought and combined stress. RNA-sequencing analysis demonstrated that many genes involved in the defense response, photosynthesis, metabolic process, etc. are differentially expressed in response to drought and heat. However, 1468 and 1220 up-regulated and 1146 and 686 down-regulated genes were confirmed as overlapping differentially expressed genes at 8 h and 24 h after treatment, and these genes are mainly involved in transport, binding and defense response. Furthermore, we compared the heat, drought and the combined stress-responsive genes and identified potential new targets for enhancing stress tolerance of soybean. Comparison of single and combined stress suggests the combined stress did not result in a simple additive response, and that there may be a synergistic response to the combination of drought and heat in soybean.